IMPROVE COGNITIVE ABILITIES AND LEARNING MOTIVATION STUDENT IN ELEMENTARY SCHOOL WITH SCIENTIFIC APPROACHES AND STORYTELLING ACTIVITIES - Lumbantobing, Septina Severina (International Journal of Educational Management and Innovation, 2020)
This research has been conducting to get a picture of improving cognitive abilities and learning motivation of students who get natural science subjects in elementary schools with a scientific approach and storytelling activities. The study has been conducting using quasi-experimental methods with a randomized one-group pretest-posttest design. The population is all grade IV students of SD Negeri 7 Jakarta. A sample of one class has been selecting by random cluster sampling. The sample of this research was class IV C, with 30 students. Test instruments in the form of essay tests were 15 items, and learning motivation questionnaires were 12 items with five options using the Likert Scale. The data has been processing with the help of SPSS 22 software. The results showed that there was an increase in students' cognitive abilities with a gain value of 0.55 in the medium category. Student learning motivation has been obtaining an increase of 85.76% in the top category.